High-intensity focused ultrasound in the treatment of breast tumours - Peek, M; Wu, F (Cancer Intelligence, 2018)
High-intensity focused ultrasound (HIFU) is a minimally invasive technique that has been used for the treatment of both benign and malignant tumours. With HIFU, an ultrasound (US) beam propagates through soft tissue as a high-frequency pressure wave. The US beam is focused at a small target volume, and due to the energy building up at this site, the temperature rises, causing coagulative necrosis and protein denaturation within a few seconds. HIFU is capable of providing a completely non-invasive treatment without causing damage to the directly adjacent tissues. HIFU can be either guided by US or magnetic resonance imaging (MRI). Guided imaging is used to plan the treatment, detect any movement during the treatment and monitor response in real-time. This review describes the history of HIFU, the HIFU technique, available devices and gives an overview of the published literature in the treatment of benign and malignant breast tumours with HIFU.